Binding of desloratadine and atenolol with bovine serum albumin and their in-vitro interactions - Shihab-us-Sakib, Khondoker; Islam, Mohammad A.; Moniruzzaman, M.; Hussein, Anwar; Hossain, M. Mahboob; Mazid, Mohammad A. (© 2012 Ars Pharmaceutica, 2016)
This article was published in the Ars Pharmaceutica [© 2012 Ars Pharmaceutica] The Journal's website is at: http://farmacia.ugr.es/ars/ars_web/controldescargas.php?763.